Mapping out the scientific literature on extraction and socket preservation: A Scopus based analysis (1968–2020) - Khalid Almas; Shakil Ahmad; Shafiq Ur Rehman; Shakil Ahmad; Faisal Aljofi; Allauddin Siddiqi (Saudi Dental Journal)
Purpose: This study aimed to investigate the current state of research on tooth extraction socket preservation. The main aim of this study was to consolidate the research published on extraction socket preservation from 1968 to 2020 in Scopus indexed journals. Methodology: The bibliometric method, a quantitative analysis investigating publishing trends and patterns, was used. Scopus database was used to retrieve the bibliographic records of published scholarly output. The analysis was performed using software and visualization tools like MS Excel, VOSviewer, Cite Space, Biblioshiny (RStudio), and BibExcel. Results: The result showed a gradual increase in research, whereby a substantial increase was observed from 2005 to 2006. Six hundred nineteen articles were published in 173 journals with total citations of 12091. Most published articles were from the USA, Italy, Germany, and China. The authorship pattern showed an interdisciplinary and collaborative approach among researchers. Conclusion: This bibliometric analysis can guide researchers, funding agencies, industry, and institutions.